Aeolian dust distribution, elemental concentration, characteristics and its effects on the conversion efficiency of crystalline silicon solar cells. (May 2023) - Ndeto, Martin Paul; Wekesa, David Wafula; Njoka, Francis; Kinyua, Robert
Abstract: Exposure of PV modules to ambient environmental conditions like dust deposits, has some deleterious effects on peak power ( P max ) and overall conversion efficiency ( η ). This study investigates the effect of module height, tilt, and orientation on the rate of dust deposition on the surfaces of PV modules. Consequently, the effect of different dust categories on P max and η are investigated. North facing module surfaces are observed to exhibit higher deposition rates in southerly winds. A significant decrease in conversion efficiency of 1.30%, 1.74%, 4.05%, 2.74% and 1.38% after a fortnight are observed in modules installed in five randomly selected study sites. A higher decrease in efficiency on average after a fortnight is observed in sites having traces of anthropogenic particles on dust samples collected from the PV surfaces with minimal effects observed in sites having biogenic and geogenic particles. Abundance of anthropogenic dust particles coupled with mild tilt and leeward orientation led to a higher maximum power and efficiency degradation rate.